Pembangunan Website untuk Penjadwalan Maintenance Menggunakan Algoritma Priority Schedulling - Harahap, Muhammad Abarorya; Rangkuti, Yulita Molliq; AS, Mansur; Indra, Zulfahmi; Saputra, Kana (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
PTPN II Sugar Factory (PG.II) is a company that produces sugar which often experiences difficulties in producing sugar that is not time efficient due to frequent unexpected damage to the machine, which results in a reduced amount of time used to produce sugar. One of the causes of machine damage at PTPN II Kwala Madu is the absence of an information system about scheduling machine maintenance so that production machine damage occurs. The purpose of performing maintenance is so that the network distribution capability can meet the needs of the company, maintaining quality at the right level to meet what is needed by the production itself. Maintenance also aims to achieve the lowest possible cost level and avoid maintenance activities that can endanger the safety of the workforce or employees. help reduce usage or deviations beyond the limit and maintain the capital that has been invested during the specified time in accordance with the policies of the company or organization. The stages of this research are analyzing needs, designing / modeling a scheduling system with the Priority Schedulling algorithm, followed by programming, software testing and testing. Global system design using UML modeling language consisting of Usecase Diagram, Activity Diagram, Class Diagram, and Bari Diagram